2018
DOI: 10.2147/ijn.s168554
|View full text |Cite
|
Sign up to set email alerts
|

The effects of amine-modified single-walled carbon nanotubes on the mouse microbiota

Abstract: BackgroundAmine-modified carbon nanotubes are drug delivery platforms with great potential that have not yet been applied in human clinical trials. Although modified nanotube vectors have the ability to carry multiple effectors, targeting agents, and even wrapped RNA, reports on unmodified, insoluble carbon nanotubes have highlighted inflammation in organs, including the intestine, with disruption of its resident microbiota. Disruption of the microbiota may allow for colonization by pathogenic bacteria, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Strikingly, several studies found no significant effect of ENMs (Au, CuO, Ag and lysine-modified SWCNTs) on intestinal immunity ( 17 , 20 , 21 , 27 , 29 , 87 ). One possibility is that most ENMs may be rapidly excreted following ingestion, so few accumulate in the GIT and they are insufficient to modulate the immune responses.…”
Section: The Potential Effect Of Enm-altered Microbiota On Intestinal Inflammationmentioning
confidence: 96%
See 3 more Smart Citations
“…Strikingly, several studies found no significant effect of ENMs (Au, CuO, Ag and lysine-modified SWCNTs) on intestinal immunity ( 17 , 20 , 21 , 27 , 29 , 87 ). One possibility is that most ENMs may be rapidly excreted following ingestion, so few accumulate in the GIT and they are insufficient to modulate the immune responses.…”
Section: The Potential Effect Of Enm-altered Microbiota On Intestinal Inflammationmentioning
confidence: 96%
“…Enrichment of Lactobacillus was found in these works, again highlighting the protective role of SCFA-producers in epithelium integrity and anti-inflammatory responses. Strikingly, several studies found no significant effect of ENMs (Au, CuO, Ag and lysine-modified SWCNTs) on intestinal immunity (17,20,21,27,29,87). One possibility is that most ENMs may be rapidly excreted following ingestion, so few accumulate in the GIT and they are insufficient to modulate the immune responses.…”
Section: The Potential Effect Of Enm-altered Microbiota On Intestinal Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…SWCNT-Lys-NH 2 29, as shown in Scheme 7 was prepared from SWCNTs 1 and H-Lys(Boc)-OH 28 in the presence of paraformaldehyde (PFA) and TFA to afford lysine-modified SWCNTs 29, which were nontoxic and did not have the primary influence on the microbiota [26,27]. The main strategy was the covalent functionalization of SWCNTs with ciprofloxacin by spacer support to enhance the hydrophilichydrophobic stability and gain a fresh stable nano-antibiotic compound, which is biocompatible (Scheme 11).…”
Section: Swcnts Functionalized By Lysinementioning
confidence: 99%